1994
DOI: 10.1037/0022-3514.66.3.570
|View full text |Cite
|
Sign up to set email alerts
|

Interactions in predicting mood from extraversion and neuroticism.

Abstract: Many researchers have found evidence that, when only marginal distributions are examined, extraversion is related primarily to positive affect, whereas neuroticism is related primarily to negative affect. Recent findings have suggested that extraversion and neuroticism interact in predicting mood so that marginal relations could be misleading. The present study used extraversion (and its components, sociability and impulsivity) along with neuroticism in regression equations including interactive and curvilinea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
3
7

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 33 publications
4
56
3
7
Order By: Relevance
“…Recent work suggests that extraversion and neuroticism may jointly influence affective responding under certain conditions (e.g., Derryberry & Reed, 1994;McFatter, 1994;Wallace, Newman, & Bachorowski, 1991). We therefore conducted preliminary analyses in which extraversion, neuroficism, and their interaction were entered as predictors of affective reports.…”
Section: Notesmentioning
confidence: 99%
“…Recent work suggests that extraversion and neuroticism may jointly influence affective responding under certain conditions (e.g., Derryberry & Reed, 1994;McFatter, 1994;Wallace, Newman, & Bachorowski, 1991). We therefore conducted preliminary analyses in which extraversion, neuroficism, and their interaction were entered as predictors of affective reports.…”
Section: Notesmentioning
confidence: 99%
“…13 Johnson ve Ostendorf neşeli, enerjik, istekli, arkadaş canlısı gibi sıfatların pozitif olarak, dikkatsizlik, düşüncesizlik gibi özelliklerin de negatif olarak bu faktör içerisinde yer aldıklarını bildirmişler-dir. 14 Hogan, faktörün sosyallik ve girişkenlik olarak ikiye ayrılması gerektiğini, 15 McFatter, dışadönüklüğün dürtüsellik yönünün daha kuvvetli ilişkiler gösterdi-ğini, 16 MacDonald da dışadönüklerin ödüle duyarlı olduklarını belirtmişlerdir.…”
unclassified
“…Whereas some research has found evidence for an interaction between Extraversion and Neuroticism in predicting positive and negative affect (McFatter, 1994), other research has not supported this finding (Allik & Realo, 1997;Rusting & Larsen, 1997).…”
Section: Positive and Negative Affectmentioning
confidence: 61%
“…(Allik & Realo, 1997;Berry & Hansen, 1996;McFatter, 1994;Meyer & Shack, 1989) and fundamental to theoretical formulations of the structure of affect (Costa & McCrae, 1992;Watson et al, 1988). One of the lines of evidence for the conceptualization of positive and negative affect as independent dimensions is that positive affect is related to Extraversion but negative affect is not (Allik & Realo, 1997;Diener & Emmons, 1985;; it is expected that this finding will be replicated.…”
Section: Hypothesismentioning
confidence: 85%
See 1 more Smart Citation